2015
DOI: 10.1186/s12913-015-0998-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of patient education programs on medication use among asthma and COPD patients: a propensity score matching with a difference-in-difference regression approach

Abstract: BackgroundAdherence to medication is one of the critical determinants of successful management of chronic diseases including asthma and chronic obstructive pulmonary disease (COPD). Given that poor adherence with self-management medication is very common among asthma and COPD patients, interventions that improve the use of chronic disease management medications for this patient group have potential to generate positive health outcomes. In an effort to improve asthma and COPD care, the Lung Association of Saska… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…Education should be structured to ensure that the measurements are inter-comparable. The education should consider the patients' capabilities, so that the content can be acquired, and it has cost-effective long-term effects: less frequent exacerbations result in decreased use of healthcare resources [29].…”
Section: Discussionmentioning
confidence: 99%
“…Education should be structured to ensure that the measurements are inter-comparable. The education should consider the patients' capabilities, so that the content can be acquired, and it has cost-effective long-term effects: less frequent exacerbations result in decreased use of healthcare resources [29].…”
Section: Discussionmentioning
confidence: 99%
“…; Ling et al. ; Lo et al., ; Rankin et al., ; Sari and Osman, ; Warden et al., ). However, some programmes show only minimal improvements (Agren, ),…”
Section: Taxonomy Of Health Care Programmesmentioning
confidence: 99%
“…Evidence suggests that when properly targeted, patient education can lead to improved health outcomes and costsavings (Expert Panel on effective ways of investing in Health (EXPH), 2014; Hakanson et al2011;Ling et al 2012;Lo et al, 2009;Rankin et al, 2014;Sari and Osman, 2015;Warden et al, 2014). However, some programmes show only minimal improvements (Agren, 2013),…”
Section: Who Health In Prison Popula On Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Lorig et al found that a health education program for self-management in patients with chronic arthritis resulted in a decline in pain, physician visits, and costs [1]. Sari & Osman found that health education and greater access to spirometry resulted in increased medication use in COPD and asthma patients [2]. A systematic review (Cochrane review) looking at interventions aiming to improve medication adherence showed that patient education interventions improve medication adherence, decrease emergency department (ED) visits, and hospital admissions [3].…”
Section: Introductionmentioning
confidence: 99%